Volatilization of ammonia in systems of treatment of swine manure with aquatic macrophytes - C. D. Pinaffi; C. H. Santos (Brazilian Journal of Biology, 2018)
Abstract The usage of aquatic plants represents an alternative in the treatment of residues originating from swine. In these systems, one of the N removal methods is the ammonium (NH4 +) uptake and volatilization of ammonia (NH3). In this way, the objective of this work was to evaluate the volatilization rates of NH3 in waste treatment systems swine fluids (SSF) with aquatic macrophytes, as well as the concentration of NH 4+ present in the swine fluids. The experiment was carried out at Campus II/UNOESTE. The treatment systems were composed of 16 boxes of PVC and characterized as: T1 = Control sample 50% of SSF/50% of water; T2 = 50% SSF/50% water + Eichhornia crassipes (Mart.) Solms; T3 = 50% SSF/50% water + Pistia stratiotes L.; T4 = 50% SSF/50% water + Salvinia auriculata Aubl. The design was randomized blocks, with 4 treatments and 4 replicates. The hydrogen potential (pH) and the NH4 + content of the effluent were analyzed weekly, and the volatilization of NH 3 by means of collectors installed in each treatment unit. The presence of aquatic macrophytes promoted the reduction of NH4+ concentration and of the pH values of swine fluids, and this resulted in the reduction of NH3 volatilization rates to the environment, with emphasis on the system with Eichhornia crassipes (Mart.) Solms, which presented the lowest rate of volatilization.